Regional Economic Development of the PRC through the Data of the World Economic Statistics - Andrei V. Ostrovskii (Население и экономика)
The article analyzes the results of a forecast on the socio-economic development of Chinese regions made ten years ago in a collective monograph by the Institute of the Far East of the Russian Academy of Sciences. These results are compared with data from various countries in terms of gross domestic product (GDP) and GDP per capita. Based on statistical data from the National Bureau of Statistics (NBS) of China for 2022, it was determined that China’s GDP ranks first globally in terms of purchasing power parity (PPP) and second in terms of the dollar exchange rate. More than half of China’s GDP continues to be concentrated in the coastal regions, which host the main “growth poles” of the Chinese economy: the Beijing – Tianjin – Hebei region, the Yangtze River Delta (encompassing Shanghai, northern Zhejiang, and southern Jiangsu), and the Pearl River Delta (southern Guangdong, including the Shenzhen and Zhuhai free economic zones). According to GDP figures at the dollar exchange rate, not only Guangdong but also Jiangsu has surpassed Russia. Overall, in terms of GDP, most of China’s coastal regions have reached the level of Eastern European countries and Portugal. Over the past decade, the gap in gross regional product (GRP) between the coastal regions and the central and western regions has significantly decreased. Most of China’s provinces now achieve GRP levels of $4-8 trillion per year (or $615-1.230 billion), surpassing the GDP figures of most countries worldwide. However, the gap between the coastal regions and the northeastern provinces (Heilongjiang, Jilin, and Liaoning) has widened. The GRP per capita in these three northeastern provinces is now lower than in the six central provinces. To stimulate economic development in the western and central regions, as well as in the Northeast of China, the One Belt, One Road initiative was launched in 2013. This initiative aims not only to enhance the foreign economic relations of these lagging territories but also to ensure their accelerated growth by fostering new “growth poles” within these regions. The establishment of such poles is expected to drive faster development in these areas, thereby narrowing the economic gap between them and the more advanced coastal regions.